Liver transplantation for giant hemangioma of the liver: A case report and review of the literature - Zhao, Yun; Li, Xiu-Ping; Hu, Yuan-Yuan; Jiang, Ji-Chang; Zhao, Li-Jin (Frontiers in Medicine, 2022)
Large benign hepatic masses as a rare indication for liver transplantation have been reported less frequently. These liver transplantations are complex, with high intraoperative bleeding, high perioperative complication rates and high mortality rates due to difficulties in visualization, especially when they have undergone various percutaneous operations or open surgery resulting in severe perihepatic adhesions. Here is a case report of a patient admitted to our hospital who underwent liver transplantation after suffering from a giant hemangioma in liver transplantation for 10 years and who had received multiple interventional treatments ineffective in the past.